Effect of Urea Application on Corn Productivity: A Meta-Analysis - Riadi, Septa; Rohmah Nurazizah, Ghoitsa; Wakano, Deli; Fadilah, Ratanawaty (Jurnal Ilmiah Pertanian dan Peternakan, 2023)
Purpose: This study provides a meta-analysis of previous research investigating the effect of urea application on corn productivity. The aim is to develop a comprehensive and robust understanding of the relationship between urea use and corn yield, offering evidence-based recommendations for fertilizer management. Research Methodology: The meta-analysis was conducted through several stages, including determining the reference component of the literature search, collecting and tabulating relevant data, standardizing datasets from multiple studies, and analyzing the results using the OpenMEE software to synthesize findings across different research sources. Results: The findings indicate that urea application significantly improves corn productivity. The positive impact on yield is even greater when urea is combined with other fertilizers, highlighting the importance of integrated fertilization practices. Furthermore, the timing of urea application is shown to be critical, with pre-planting application producing better results compared to post-planting application, suggesting that nutrient availability during early crop development is essential for optimal growth. Conclusion:This study concludes that proper urea application, especially when combined with other fertilizers and applied before planting, can substantially enhance corn yield. Optimizing fertilizer use through recommended dosage and timing contributes to improved agricultural productivity. Limitations: The study is limited to research using combined fertilization approaches, favorable climatic conditions, and controlled agricultural settings such as demonstration plots, which may not fully represent diverse field conditions. Contribution: The results provide practical guidance for farmers and agricultural practitioners to improve fertilizer management strategies, maximize corn productivity, and support evidence-based agricultural decision-making.